Makna Passempa’ Dalam Je’ne’-Je’ne’ Sappara’ Oleh Masyarakat Balangloe Tarowang Kecamatan Tarowang Kabupaten Jeneponto - Putri, Sulfiana Mansyur; M, Rezky Putri Wira Utami (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
The research entitled "The Meaning of Passempa in the Je'ne'-Je'ne' Sappara' Ritual by the Balangloe Tarowang Community, Tarowang District, Jeneponto Regency" the authors try to reveal the values and meaning of passempa' for the people of Balangloe Tarowang Village, Tarowang District, Jeneponto Regency. The problems analyzed are: (1) What is the form of passempa' in je'ne'-je'ne' sappara' by the people of Balangloe Tarowang Village, Tarowang District, Jeneponto Regency, and (2) What is the meaning of passempa' in je'ne'-je' ne' sappara' by the people of Balangloe Tarowang Village, Tarowang District, Jeneponto Regency. Answering the first formulation of the problem uses the theories and opinions of several theater leaders regarding forms. Responding to the second formulation of the problem, namely the interpretation of symbolic forms as expressions of contextualization within the overall structure of meaning by Geertz. This research is qualitative in nature. The data were collected through literature study, direct observation and interviews. The results of the research using approaches related to the theory of form, structure, and the concept of interpretation of meaning prove that passempa' by the people of Balangloe Tarowang Village in Tarowang District, Jeneponto Regency includes elements of performing arts spectacle as well as other performing arts as well as indicating the values of the Bugis- Makassar contained in the meaning passempa'.